PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DALAM RANGKA MENYAMBUT ERA NEW NORMAL - Kori Puspita Ningsih; Angga Eko Pramono; Laili Rahmatul Ilmi; Ratna Prahesti; Tri Sunarsih; Ida Nursanti; Syairaji (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
To reduce the death rate and control the transmission of Covid-19 disease, promoting a healthy lifestyle program is needed. The community services program aimed to improve local community knowledge and attitudes in responding to Covid-19 at New Normal Era. Our participants were the village officer representative and cadres of Kanoman Hamlet, Banyuraden, Gamping, Sleman. We provided counseling and education program regarding a clean and healthy lifestyle. In addition, we conducted a training program for village officers on how to use medical examination tools, provide medical equipment assistance, and evaluate the program's success. The results show that the local community finally realized the importance of a clean and healthy lifestyle. Also, an education program on a clean and healthy lifestyle, cough etiquette, correct hand washing steps, and other health protocols are going to be continuously provided by village officers and cadres to the community through routine meeting forums. The training and provision of medical equipment also dramatically supports the implementation of health protocols in the hamlets of Kanoman, Banyuraden, Gamping, Sleman. Finally, it is necessary to provide further support and encourage the local community for the continuous prevention of covid-19.